Impressive journey of TAVI so far, but miles to go - Shah, Rikin; Dave, Bhargav (International Journal of Research in Medical Sciences, 2018)
Valve replacement is mandatory for AS patients owing to its progressive nature leading to continuous valve degeneration. However, surgical replacement cannot be opted for majority of patients due to old age and affiliated co-morbidities. Over the recent years, AS treatment in high-risk patient population favors a newer, less-invasive method of transcatheter aortic valve implantation (TAVI). The main objective of this review is to revisit all the relevant aspects of TAVI to treat AS in high-risk patients and to assess its possibility as a first-line treatment approach even for low-risk AS patients. We searched PubMed, Google Scholar, Medline and ClinicalTrials.gov to identify all the relevant randomized controlled trials (RCTs) assessing the outcomes of TAVI vs. surgical mode of valve replacement. This method is found to be very safe and reproducible in many landmark clinical trials involving high-risk patients, demonstrating superior or, at least, comparable outcomes vs. surgical mode of treatment. This led to a trend of testing TAVI in lower-risk patient population as well to expand its treatment indication profile.